Confirmatory Factor Analysis of Social Support Scale Among University Students: Analisis Faktor Konfirmatori Skala Dukungan Sosial Pada Mahasiswa - Muhaimin Abdillah; Nanda Alfan Kurniawan; Kmas M. Eka Fhitrah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Elevated levels of social support are not only instrumental in assisting university students with managing developmental stress but are also closely associated with their psychological well-being. However, within the Indonesian higher education context, the psychometric evaluation, particularly the construct validity and reliability of social support instruments remains underexplored. This study aimed to assess the construct validity and examine the factorial structure of a social support scale among Indonesian undergraduate students. Utilizing Confirmatory Factor Analysis (CFA), data from 145 participants were analyzed to evaluate the model fit and factor structure. Initial analysis indicated that, although the hypothesized three-factor model exhibited substantial item loadings, its overall model fit did not meet acceptable thresholds, suggesting a need for refinement. Subsequent CFA of the revised model confirmed an improved fit to the empirical data. Ultimately, only seven items demonstrated satisfactory psychometric properties in this student population. These results offer valuable implications for improving both assessment practices and the quality of counseling services within university settings.